Comparison of In Vitro Fertilization Outcomes between Normal and T-Shaped Uteri, Diagnosed by Hysterosalpingography in Women with infertility: A Retrospective Cohort Study - Fattaneh Pahlavan; Shohreh Irani; Mehri Mashayekhi; Samira Vesali; Fatemeh Niknejad; Firoozeh Ahmadi; Narges Bagheri-Lankarani (International Journal of Fertility and Sterility)
Background: T-shaped uterus is a subclass of dysmorphic uteri according to the European Society of Human Reproductionand Embryology (ESHRE) classification. A T-shaped uterus might be related to poor reproductive outcomesor pregnancy complications. We aim to compare the success rates of in vitro fertilization (IVF) between individualswith a normal uterus and those with a T-shaped uterus identified through Hysterosalpingography.Materials and Methods: A retrospective cohort study was done in Royan Institute, Iran, in April 2020-April 2021.In line with the criteria for inclusion and exclusion, 468 cases were selected. Inclusion criteria were as follow: womenof 20-45 years old, primary infertility, no repeated implantation failure (RIF), embryo quality “grade A” or “grade B”(freeze), and no consumption of smoking or alcohol. Patients with uterine fibroid, polyp, metabolic disorders, previousuterine surgery were excluded. Based on the hysterosalpingography (HSG) images, the patients were categorizedas: “T-shaped uterus” or “normal uterus”. IVF outcomes including positive or negative chemical pregnancy wereentered into SPSS software. Using the Chi-square test, the success rate of IVF in those groups was compared.Results: Of 468 cases, 91 cases had T-shaped uterus and 377 cases had normal uterus. The mean age of patients was34 ± 3. The frequency of positive chemical pregnancy in the T-shaped uterus group was 42.9%, but 48% in the normaluterus group. The distribution of positive clinical pregnancy was 34.06% in the T-shaped uterus group and 46.1% inthe normal uterus group. The distribution of failed pregnancies was 20.5% in women with T-shaped uteri and 19.8%in the normal uterus group (P=0.867). There was no significant difference observed between the two groups.Conclusion: The success rate of IVF and pregnancy outcomes of patients in the T-shape and normal groups were notfound to be statistically significantly different.